Petrographic and Lithogeochemical Characterization of the Tanguá Alkaline Suite, Poços de Caldas-Cabo Frio Alignment, Rio de Janeiro State - Paiva Alves, João Pedro; Holanda, Werlem; Costa dos Santos, Anderson; Maia Teodoro, Marco Aurélio (Anuário do Instituto de Geociências, 2025)
The Tanguá Alkaline Suite (RJ) consists of nepheline syenites, syenites, alkaline magmatic breccias, and phonolites, and it is inserted in the magmatic alignment of Poços de Caldas-Cabo Frio (ca. 84-49 Ma) that extends in the WNW-ESE direction, in the center portion of the Ribeira Belt (ca. 620-520 Ma). The Tanguá intrusion exhibits a concentric zoning characterized by the variation in the proportions of orthoclase, nepheline, and pseudoleucite. This variation is due to the association with the embedding rock. The contact occurs between an unsaturated phase in silica (nepheline syenite magma) and a supersaturated phase in silica (metamorphic rocks of the basement). The project aims to present analytical studies applied to the geological interpretation of the Alkaline Tanguá Suite, using petrographic, X-ray diffraction (XRD), and geochemistry data. The petrographic analysis demonstrated that the main lithotype is nepheline syenite, composed mainly of alkali feldspar and nepheline, with three distinct textures: medium, coarse, and porphyritic. These textural variations suggest different conditions of temperature, pressure and depth during the magma crystallization. X-ray diffraction data suggest the occurrence of orthoclase, fluorine-arfvedsonite, and hedenbergite. Geochemical data show a lithotype undersaturated in silica and rich in potassium and sodium.